RETROSPECTIVE REVIEW OF STUDIES OF STRATEGIC MANAGEMENT OF AUTOMOTIVE ENTERPRISES - Mishak, T. (Global Prosperity, 2024)
The article is dedicated to the analysis of the innovative activity of automotive manufacturing enterprises (AME) in Ukraine in the context of economic challenges and strategic management. The authors examine the current state of AME and emphasize the importance of implementing innovative technologies as a key factor for the enterprises’ competitiveness. The historical development of Ukraine’s industrial sector is described, beginning with the Soviet period, and the key challenges the industry has faced in the post-crisis period, including the COVID-19 pandemic and Russian military aggression. The article also discusses problems such as insufficient innovation activity, outdated material and technical bases, and limited financial resources. The authors highlight the importance of state support and the implementation of modern management approaches to stimulate innovation. Special attention is given to the impact of IT companies on the development of the automotive sector through the integration of cutting-edge digital solutions into production processes and enhancing interaction between AME and the IT sector.